IL28B polymorphisms predict response to therapy among chronic hepatitis C patients with HCV genotype 4. Issue 1 (24th May 2012) - Antaki, N.; Bibert, S.; Kebbewar, K.; Asaad, F.; Baroudi, O.; Alideeb, S.; Hadad, M.; Abboud, D.; Sabah, H.; Bochud, P.‐Y.; Negro, F.
<x xml:space="preserve">Abstract</x> Summary. Genetic polymorphisms near IL28B are associated with spontaneous and treatment‐induced clearance of hepatitis C virus (HCV). Our objective was to assess the predictive value of IL28B polymorphisms in the treatment of chronic hepatitis C of patients with HCV genotypes 4, for which data are currently limited. We analysed the association of IL28B polymorphisms with the virological response to treatment among 182 naïve chronic hepatitis C patients with HCV genotype 4, all from Syria. Associations of alleles with the response patterns were evaluated by univariate analysis and multivariate logistic regression, accounting for all relevant covariates. Sustained virological response (SVR) was achieved in 26% of rs8099917 TG/GG carriers compared with 60% of TT carriers (P < 0.0001) and 35% of rs12979860 CT/TT carriers compared with 62% of CC carriers (P = 0.0011). By multivariate analysis, the association between rs8099917 and SVR remained significant (OR = 0.19, 95% CI 0.07–0.50, for TG/GG vs TT, P = 0.0007), with the only significant covariate being advanced fibrosis (OR = 0.13, 95% CI 0.04–0.37, P = 0.0002). In conclusion, IL28B polymorphisms are the strongest predictors of response to therapy among chronic hepatitis C patients with HCV genotype 4.